2014
DOI: 10.1111/jopr.12207
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Apple Cider Vinegar on Candida Species Involved in Denture Stomatitis

Abstract: Apple cider vinegar showed antifungal properties against Candida spp., thus representing a possible therapeutic alternative for patients with denture stomatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 39 publications
0
22
1
Order By: Relevance
“…ACV also decreased blood triglyceride and very low density lipoprotein levels in rats which had induced cholesterol induced hepatic steatosis 33 . In an infection induced model of denture stomatitis, ACV addition resulted in anti-fungal activity against Candida Spp which was comparable to nystatin in terms of reducing microbial adherence and destruction 37 .…”
Section: Discussionmentioning
confidence: 94%
“…ACV also decreased blood triglyceride and very low density lipoprotein levels in rats which had induced cholesterol induced hepatic steatosis 33 . In an infection induced model of denture stomatitis, ACV addition resulted in anti-fungal activity against Candida Spp which was comparable to nystatin in terms of reducing microbial adherence and destruction 37 .…”
Section: Discussionmentioning
confidence: 94%
“…Recent clinical studies have revealed anti-biofilm efficacy of agents derived from plants [18][19][20][21], and importantly, an absence of detrimental effects on denture base materials [20,21]. Cinnamon oil is an extract from the plant Cinnamon cassia, whilst citronella is derived from Cymbopogon winterianus.…”
Section: Introductionmentioning
confidence: 99%
“…23 On the literature, it is noticed the great interest in new natural actives and herbal medicines, due its antimicrobial properties and/ or antiinflammatory, being, in the last years, many them reported. Among them, it can be found spread describe actives like vinegar from the apple, 25 black-pepper, 19 garlic, sage, mastic gum, 23 melaleuca, rosemary, citronella, 20 propolis and pomegranates. 26 As emphasis, it is the grape (Vitis vinifera).…”
Section: Discussionmentioning
confidence: 99%